Comparing the methylomes of two genealogically linked Russian wheat aphid biotypes using whole genome bisulfite sequencing - du Preez, Pieter Herodus (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.